Kinerja Keuangan Bank Mandiri Tbk Sebelum Dan Sesudah Stock Split - N Kalbiyati, Ridha; Juniar, Asrid; Adi, Setijo; Sofyaun, Ashari (Fakultas Ekonomi Universitas Balikpapan, 2024)
This study aims to analyze the financial performance of Bank Mandiri Tbk before and after the stock split. The type of research used is quantitative research. The objects in this study are the financial statements and market performance (stock prices) of PT Bank Mandiri Tbk before and after the stock split. The sample is the financial statements for 2014-2016 as the period before the stock split and 2018-2020 after the stock split. The results of the study showed no difference in financial performance interpreted by the Current Ratio, Debt Equity Ratio, Return on Equity, Total Assets Turn Over both before and after the Stock Split policy.